A high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer and a method for preparing the same
By reacting ammonia-terminated polysiloxanes with aromatic dianhydrides to generate anhydride-terminated prepolymers, followed by chain extension, imidization, and metal coordination crosslinking, the problem of insufficient mechanical properties of high-temperature thermoplastic elastomers at high temperatures is solved, achieving high strength and thermoplastic properties at high temperatures.
Patent Information
- Application Number
- CN202411478420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Existing high-temperature thermoplastic elastomer materials perform poorly in terms of mechanical properties and high service temperatures, especially in terms of insufficient tensile strength and elongation at break, and traditional chemical crosslinking causes the materials to lose their thermal processability.
Ammonia-terminated polysiloxanes are reacted with aromatic dianhydrides to generate anhydride-terminated poly(siloxane-amic acid) prepolymers, which are then chain-extended with carboxyl-substituted aromatic diamines and imidized. Finally, high-strength poly(siloxane-imide) thermoplastic elastomers are formed through metal coordination crosslinking.
It improves the tensile strength and elongation at break of the material, ensuring good mechanical properties and thermoplasticity at high temperatures, and has excellent temperature resistance.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0005096698330000031
Abstract
Description
Technical Field
[0001] This invention relates to a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer and its preparation method, belonging to the field of organosilicon polymer synthesis technology. Background Technology
[0002] Thermoplastic elastomers are a class of elastomers that exhibit the elasticity of rubber at room temperature and can be plasticized and molded at high temperatures. They are typically formed by crystallization or high glass transition temperatures (T0). g Poly(siloxane-imide) is composed of hard segments and highly elastic soft segments. At room temperature, the hard segments form a physical cross-linking network through intersegmental interactions, acting as a physical cross-linking and reinforcing filler, while the molecular chains of the soft segments impart high elasticity to the material. Linear polysiloxanes possess excellent high and low temperature resistance, aging resistance, weather resistance, hydrophobicity, flame retardancy, and physiological inertness, making them ideal soft-segment polymers. Polyimides, due to their aromatic rings and cyclic imide structures, possess excellent high-temperature resistance, flame retardancy, and dimensional stability. Poly(siloxane-imide), using polysiloxane as the soft segment and polyimide as the hard segment, combines the advantages of both polymers, making it an ideal thermoplastic elastomer material.
[0003] Given the specific requirements of some high-temperature applications, there is a need to develop poly(siloxane-imide) thermoplastic elastomers that combine excellent mechanical properties with high operating temperatures. This requires materials to maintain good dimensional stability at high operating temperatures, i.e., to have high plasticizing temperatures. Since non-polar organosilicon polymers have poor compatibility with highly polar polyimides, their reaction is prone to sharp phase separation. Relying solely on the interactions between polyimide molecular chains is insufficient to obtain polysiloxane-polyimide thermoplastic elastomers with ideal comprehensive properties. Chinese patent document CN111154107A discloses a polysiloxane-polyimide thermoplastic elastomer, which involves dissolving and mixing a diamino-terminated polysiloxane, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, and a chain extender in a polar solvent, reacting them at room temperature to obtain a colorless and transparent linear polysiloxane-polyamic acid block copolymer. Subsequently, imidization is performed at high temperature, followed by cold pressing to obtain the thermoplastic elastomer. However, the tensile strength of the material obtained by this method is <5.5MPa and the elongation at break is <105%, which is not ideal in terms of mechanical properties. Mohamed Kreaet.al., Polymer International 62 (2013): 1413-1424[J] reported the synthesis of poly(siloxane-imide) membrane material similar to organophilic membranes and gas permeation membranes by solution imidization of amino-terminated polydimethylsiloxane with fluorinated aromatic compounds containing anhydride and amine functionalization. However, the tensile strength of the obtained material is ≤8.0MPa. Xingzhong Fang et al., Journal of Applied Polymer 129(2013):3718-3727[J] reported the synthesis of a series of linear poly(imide-siloxane) thermoplastic elastomers by reacting thioether-bridged aromatic dianhydrides, ether-bridged aromatic diamines, and amino-terminated polydimethylsiloxanes. The highest tensile strength reached 33.3 MPa and the elongation at break was 124%. However, its elasticity was still not ideal, and its thermoplasticity was not explored.
[0004] Crosslinking linear poly(siloxane-imide) molecules using chemical covalent bonds can improve the heat resistance of materials to some extent. Chinese patent documents CN109679495A, CN109517172A, and CN114685790A disclose the introduction of linear polysiloxanes into polyimide molecules, followed by the use of epoxy resins, isocyanates, acrylates, etc., as chemical crosslinking agents to chemically crosslink the linear polyamic acid. Although this type of chemical covalent crosslinking can improve the heat resistance of materials to some extent, the crosslinked materials lose their heat-processing properties and do not fall into the category of thermoplastic elastomers. Chinese patent document CN101469063A discloses an organosilicon polyimide-polyurea elastomer, which involves reacting an amino-terminated linear polysiloxane with pyromellitic anhydride, followed by the addition of diisocyanate and alkoxysilane, and completing imidization and chemical crosslinking at high temperature to obtain the elastomer. However, the patent does not disclose the tensile strength of the material, and the material is covalently cross-linked and has no thermoplasticity. Summary of the Invention
[0005] To overcome the shortcomings and deficiencies of existing technologies and avoid the defects of traditional linear poly(siloxane-imide) thermoplastic elastomers, such as low strength, poor elasticity, and low thermoplastic temperature, this invention provides a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer and its preparation method. This invention first synthesizes anhydride-terminated poly(siloxane-amic acid) prepolymer by reacting an aminoalkyl-terminated polysiloxane with an aromatic dianhydride. Then, it undergoes a chain extension reaction with a carboxyl-substituted aromatic diamine to synthesize poly(siloxane-amic acid). Following imidization, metal coordination crosslinking is performed through the carboxyl groups between chain segments to improve the mechanical properties and thermoplastic temperature of the material, resulting in a poly(siloxane-imide) thermoplastic elastomer. The poly(siloxane-imide) thermoplastic elastomer obtained by this invention exhibits high tensile strength, good elasticity, excellent mechanical properties, and a high thermoplastic temperature, demonstrating excellent temperature resistance.
[0006] The technical solution of the present invention is as follows:
[0007] A high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer has the following general structural formula:
[0008]
[0009] Where m, x, s, h, and n are all integers greater than or equal to 1;
[0010] Ar1 and Ar2 are each independently selected from C atoms that do not contain substituents or heteroatoms. 6-16 Aromatic hydrocarbon groups or C containing S, N, O, F or Cl heteroatoms 6-16 Aromatic hydrocarbon groups;
[0011] R1, R2, R3, and R4 are each independently selected from hydrogen, straight-chain hydrocarbon groups, branched alkyl groups, or cyclic alkyl groups with 1 to 18 carbon atoms containing S, N, O, or F heteroatoms or not containing the aforementioned heteroatoms, linear or branched unsaturated hydrocarbon groups with 2 to 10 carbon atoms containing one or more unsaturated double bonds containing S, N, O, or F heteroatoms or not containing the aforementioned heteroatoms, and aromatic hydrocarbon groups with 6 to 12 carbon atoms containing S, N, O, or F heteroatoms or not containing the aforementioned heteroatoms; R1, R2, R3, and R4 may be the same or different from each other;
[0012] M is a metal ion.
[0013] According to a preferred embodiment of the present invention, in formula (I), Ar1 and Ar2 are each independently selected from... R1, R2, R3, and R4 are independently selected from hydrogen, methyl, ethyl, propyl, trifluoropropyl, cyanoethyl, phenyl, vinyl, mercaptomethyl, and mercaptopropyl, respectively; M is selected from Zn. 2+ Fe 3+ Cu 2+ Co 2+ Sn 2+ or Pb 2+ .
[0014] According to a preferred embodiment of the present invention, in formula (I), 1≤x≤200 and 1≤s≤20.
[0015] According to a preferred embodiment of the present invention, the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer has a thermoplastic temperature of 120-155°C, a tensile strength ≥35MPa, and an elongation at break ≥150%.
[0016] The preparation method of the above-mentioned high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps:
[0017] (1) In a solvent, aromatic dianhydride and amino hydrocarbon-terminated polysiloxane react to obtain a poly(siloxane-amic acid) prepolymer solution;
[0018] (2) A carboxyl-substituted aromatic diamine is added to a poly(siloxane-amic acid) prepolymer solution and reacted to obtain a poly(siloxane-amic acid) solution; a catalyst is added and an imidization reaction is carried out, followed by precipitation and drying to obtain a solid polymer poly(siloxane-imide);
[0019] (3) The solid polymer poly(siloxane-imide) is dissolved in an organic solvent, a metal salt is added, and after reaction, the solvent is removed to obtain a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer.
[0020] According to a preferred embodiment of the present invention, in step (1), the solvent is a mixture of solvent A and solvent B, wherein the volume ratio of solvent A to solvent B is (1-5):(1-5).
[0021] Preferably, solvent A is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, methyl isobutyl ketone, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, dioxane, xylene, or isopropanol; solvent B is selected from tetrahydrofuran, toluene, chloroform, dichloromethane, petroleum ether, n-hexane, or ethyl acetate.
[0022] According to a preferred embodiment of the present invention, in step (1), the aromatic dianhydride is selected from C atoms that do not contain substituents or heteroatoms. 10-20 Aromatic dianhydrides or C containing heteroatoms of S, N, O, F or Cl 10-20 Aromatic dianhydride; preferably, the aromatic dianhydride is selected from hexafluoroisopropylphthalic anhydride, 4,4'-oxobisphthalic anhydride or 3,3',4,4'-benzophenone tetracarboxylic dianhydride.
[0023] According to a preferred embodiment of the present invention, in step (1), the aminohydrocarbon-terminated polysiloxane is selected from bis(3-aminopropyl)-terminated polydimethylsiloxane, bisaminopropyl poly(methylethyl)siloxane, bisaminopropyl poly(methyltrifluoropropyl)siloxane, bisaminopropyl poly(methylphenyl)siloxane, bisaminoethyl polydimethylsiloxane, bisaminoethyl poly(methylethyl)siloxane, dicyclohexylaminopropyl polydimethylsiloxane, bisaminophenylpropyl polydimethylsiloxane, bisaminoethyl poly(methyltrifluoropropyl)siloxane, or bisaminoethyl poly(methylphenyl)siloxane. Preferably, the weight-average molecular weight of the aminohydrocarbon-terminated polysiloxane is in the range of 162–16000 g / mol, more preferably 400–1100 g / mol.
[0024] According to a preferred embodiment of the present invention, in step (1), the total mass of the aromatic dianhydride and the amino hydrocarbon-terminated polysiloxane and the volume ratio of the solvent are 50 to 200 g / L.
[0025] According to a preferred embodiment of the present invention, in step (1), the molar ratio of aromatic dianhydride to aminohydrocarbon-terminated polysiloxane is (1-4):1.
[0026] According to a preferred embodiment of the present invention, in step (1), the reaction temperature is 0–80°C, the reaction time is 1–24 h, and the reaction is carried out under stirring conditions and inert gas protection. Preferably, the reaction temperature is 20–30°C, the reaction time is 6–10 h, and the inert gas is nitrogen or argon.
[0027] According to a preferred embodiment of the present invention, in step (1), the method for preparing the poly(siloxane-amic acid) prepolymer solution includes the following steps: dissolving aromatic dianhydride in solvent A, and adding dropwise a mixture of amino-terminated polysiloxane and solvent B under stirring conditions. After the addition is complete, the poly(siloxane-amic acid) prepolymer solution is obtained through reaction.
[0028] According to the present invention, in step (1), the poly(siloxane-amic acid) prepolymer has the following structure:
[0029]
[0030] Where m and x are both integers greater than or equal to 1; Ar1, R1, R2, R3, and R4 have the same meaning as in equation (I).
[0031] According to a preferred embodiment of the present invention, in step (2), the carboxyl-substituted aromatic diamine is selected from C... 7-17 The carboxyl-substituted aromatic diamine; preferably, the carboxyl-substituted aromatic diamine is selected from 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, 2,4-diaminobenzoic acid, 2,6-diaminobenzoic acid or 5,5'-methylenediaminobenzoic acid.
[0032] According to a preferred embodiment of the present invention, in step (2), the carboxyl-substituted aromatic diamine is added to the reaction system in 2 to 3 portions, with an interval of 10 to 20 minutes between each addition.
[0033] According to a preferred embodiment of the present invention, in step (2), the molar ratio of the carboxyl-substituted aromatic diamine to the aromatic dianhydride in step (1) is 1-1.1:1.
[0034] According to a preferred embodiment of the present invention, in step (2), the reaction temperature is 0–80°C, the reaction time is 1–24 h, and the reaction is carried out under stirring conditions and inert gas protection. Preferably, the reaction temperature is 20–30°C, the reaction time is 6–10 h, and the inert gas is nitrogen or argon.
[0035] According to the present invention, in step (2), the poly(siloxane-amic acid) has the following general formula:
[0036]
[0037] Where m, x, s, and h are all integers greater than or equal to 1; Ar1, Ar2, R1, R2, R3, and R4 have the same meaning as in equation (I).
[0038] According to a preferred embodiment of the present invention, in step (2), the catalyst is selected from organic amines, organic phosphines, pyridines, benzopyridines, amidines, or organic guanidines; preferably, the catalyst is selected from one or more combinations of triethylamine, hexamethylenetetramine, pyridine, or isoquinoline.
[0039] According to a preferred embodiment of the present invention, in step (2), the molar ratio of the catalyst to the carboxyl-substituted aromatic diamine is 1:(1-2).
[0040] According to a preferred embodiment of the present invention, in step (2), the imidization reaction temperature is 60–200°C, the imidization reaction time is 1–24 h, and the imidization reaction is carried out under stirring conditions and inert gas protection. Preferably, the imidization reaction temperature is 170–190°C, the imidization reaction time is 6–10 h, and the inert gas is nitrogen or argon.
[0041] According to a preferred embodiment of the present invention, in step (2), precipitation is carried out using a mixed solution of anhydrous methanol and water, wherein the volume ratio of anhydrous methanol to water is 1:1.
[0042] According to the present invention, in step (2), the solid polymer poly(siloxane-imide) has the following general formula:
[0043]
[0044] Where m, x, s, and h are integers greater than or equal to 1; Ar1, Ar2, R1, R2, R3, and R4 have the same meaning as in equation (I).
[0045] According to a preferred embodiment of the present invention, in step (3), the organic solvent is selected from one or more combinations of tetrahydrofuran, ethyl acetate, isopropanol, toluene, chloroform, dichloromethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dioxane, or xylene.
[0046] According to a preferred embodiment of the present invention, the molar ratio of the carboxyl-substituted aromatic diamine in step (2) to the volume ratio of the organic solvent in step (3) is 0.1-1 mol / L.
[0047] According to a preferred embodiment of the present invention, in step (3), the metal salt is selected from one or more combinations of metal halides, metal nitrates, metal sulfates or organometallic salts; preferably, the metal salt is selected from iron acetylacetonate, zinc acetate, cobalt chloride, copper sulfate, lead nitrate, zinc chloride or stannous isooctanoate.
[0048] According to a preferred embodiment of the present invention, in step (3), the molar ratio of the metal salt to the carboxyl-substituted aromatic diamine in step (2) is 1:7-20.
[0049] According to a preferred embodiment of the present invention, in step (3), the reaction temperature is 20-50°C, the reaction time is 1-3 hours, and the reaction is carried out under stirring conditions.
[0050] The technical features and beneficial effects of this invention are as follows:
[0051] (1) The present invention adopts a method of prepolymerization followed by chain extension. Precisely measured amino-hydrocarbon-terminated polysiloxane and aromatic dianhydride are mixed and reacted to synthesize anhydride-terminated poly(siloxane-amide acid), which can effectively improve the sharp phase separation caused by poor interfacial compatibility between polysiloxane and polyimide, thereby ensuring good molecular weight and structural uniformity of the final polymer elastomer and improving material stability.
[0052] (2) The crosslinking method of the thermoplastic elastomer of the present invention is the combined effect of physical crosslinking and coordination crosslinking of polyimide segments. The introduction of coordination crosslinking can make the stress distribution between or within molecular chains more uniform, and at the same time strengthen the crosslinking network, so that the final thermoplastic elastomer has higher strength and thermoplastic temperature.
[0053] (3) The poly(siloxane-imide) thermoplastic elastomer prepared by the method of the present invention has a tensile strength ≥30MPa, exhibiting high tensile strength; an elongation at break ≥150%, demonstrating good elasticity; and a thermoplastic temperature above 120℃, exhibiting excellent temperature resistance. The poly(siloxane-imide) thermoplastic elastomer of the present invention has excellent comprehensive performance, ensuring sufficient mechanical properties at high operating temperatures to meet the requirements of use under special conditions. Attached Figure Description
[0054] Figure 1 The infrared spectrum of the product obtained in Example 1 of this invention is shown.
[0055] Figure 2 This is a thermoplastic temperature test diagram of the product obtained in Example 1 of the present invention. Detailed Implementation
[0056] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0057] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0058] Test instructions:
[0059] Infrared spectroscopy was performed using a Bruker Tensor 27 infrared spectrometer. Samples were compressed using potassium bromide pellets, and 16 samples were collected, with the frequency range from 4000 cm⁻¹. -1 up to 400cm -1 The resolution is 4cm. -1 .
[0060] The mechanical properties of the samples were tested using an Instron 3343 materials testing system. According to GB / T 1040-2006, the solid samples were hot-pressed at 180℃ and 15MPa for 15 minutes to obtain thin sheet samples, which were then cut into dumbbell-shaped strips. Stress-strain analysis was used to determine the mechanical properties of the materials, and at least three parallel tests were conducted.
[0061] The thermoplastic temperature of the samples was tested using static thermomechanical analysis (TMA) with a Netzsch TMA4000 instrument. The samples were cut into strips (20×10×0.5mm), a stress of 1N was applied, and the test temperature was 35℃~160℃ with a heating rate of 3℃ / min.
[0062] All tests were conducted at room temperature, normal pressure, and 50% relative humidity, unless otherwise stated.
[0063] Example 1
[0064] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps:
[0065] (1) Under an argon atmosphere, 1332.72 mg (0.003 mol) of hexafluoroisopropyl phthalic anhydride (6FDA) was added to a three-necked flask equipped with a stirrer, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was complete, the reaction was stirred at 25 °C for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0066] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the above poly(siloxane-amic acid) prepolymer solution in three portions (approximately 150 mg each time, with an interval of 10 min between each addition). After the addition was complete, the reaction was stirred at 25 °C for 8 h to obtain a poly(siloxane-amic acid) solution. 235 μL (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185 °C and stirred under argon atmosphere for 8 h. Finally, the polymer solution was added to a 1:1 mixture of anhydrous methanol and water to precipitate the polymer. The precipitate was collected and vacuum dried at 120 °C for 12 h to obtain the powdered solid polymer poly(siloxane-imide).
[0067] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran, add 20.46 mg (0.00015 mol) of ZnCl2, stir and react at 25 °C for 3 h, concentrate the reaction solution and pour it into a mold, evaporate the solvent and dry it under vacuum at 80 °C for 2 h to obtain a coordination crosslinked poly(siloxane-imide) thermoplastic elastomer. This material can be repeatedly dissolved and hot-pressed.
[0068] Fourier transform infrared spectroscopy was performed on the obtained thermoplastic poly(siloxane-imide), and the results are as follows: Figure 1 As shown. It can be seen that at 1782cm... -1 and 1724cm -1 A pair of asymmetric and symmetric C=O stretching vibration peaks appeared on the imide ring at 1384 cm⁻¹. -1 A CNC stretching vibration peak appears on the imide ring at 721 cm⁻¹. -1 A bending vibration peak on the imide ring appeared at 1093 cm⁻¹; at the same time, a bending vibration peak appeared at 1093 cm⁻¹. -1 1024cm -1 The Si-O-Si stretching vibration peak and 802 cm⁻¹ -1 The Si-C bending vibration peak is located at 1502 cm⁻¹. -1 Stretching vibration of the benzene ring, 1142 cm -1 The presence of the CF characteristic peak at the location proves that a poly(siloxane-imide) thermoplastic elastomer has been formed.
[0069] The mechanical properties of the elastomer obtained in Example 1 were measured, and the results showed that the tensile strength was 35 MPa and the elongation at break was 246%.
[0070] The thermoplastic temperature of the elastomer obtained in Example 1 was measured, and the results are as follows: Figure 2 As shown. By Figure 2 Analysis shows that the thermoplastic temperature of this thermoplastic poly(siloxane-imide) is 126.7℃.
[0071] Example 2
[0072] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps:
[0073] (1) Under an argon atmosphere, 1332.72 mg (0.003 mol) of hexafluoroisopropyl phthalic anhydride (6FDA) was added to a three-necked flask equipped with a stirrer, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 753.75 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 500 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was complete, the reaction was stirred at 25 °C for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0074] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the above poly(siloxane-amic acid) prepolymer solution in three portions (approximately 150 mg each time, with an interval of 10 min between each addition). After the addition was complete, the reaction was stirred at 25 °C for 8 h to obtain a poly(siloxane-amic acid) solution. 235 μL (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185 °C and stirred under argon atmosphere for 8 h. Finally, the polymer solution was added to a 1:1 mixture of anhydrous methanol and water to precipitate the polymer. The precipitate was collected and vacuum dried at 120 °C for 12 h to obtain the powdered solid polymer poly(siloxane-imide).
[0075] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran, add 20.46 mg (0.00015 mol) of ZnCl2, stir and react at 25 °C for 3 h, concentrate the reaction solution and pour it into a mold, evaporate the solvent and dry it under vacuum at 80 °C for 2 h to obtain a coordination crosslinked poly(siloxane-imide) thermoplastic elastomer. This material can be repeatedly dissolved and hot-pressed.
[0076] The elastomer material has the following characteristics: tensile strength of 52 MPa, elongation at break of 153%, and thermoplastic temperature of 130.2℃.
[0077] Example 3
[0078] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer is as described in Example 1, except that: in step (3), the amount of ZnCl2 used is 51.14 mg (0.00038 mol); other steps and conditions are the same as in Example 1.
[0079] The elastomer material has the following characteristics: tensile strength of 42 MPa, elongation at break of 203%, and thermoplastic temperature of 128.7℃.
[0080] Example 4
[0081] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps:
[0082] (1) Under an argon atmosphere, 930.23 mg (0.003 mol) of 4,4'-oxydiphthalic anhydride (ODPA) was added to a three-necked flask equipped with a stirrer, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was complete, the reaction was stirred at 25 °C for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0083] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the above poly(siloxane-amic acid) prepolymer solution in three portions (approximately 150 mg each time, with an interval of 10 min between each addition). After the addition was complete, the reaction was stirred at 25 °C for 8 h to obtain a poly(siloxane-amic acid) solution. 235 μL (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185 °C and stirred under argon atmosphere for 8 h. Finally, the polymer solution was added to a 1:1 mixture of anhydrous methanol and water to precipitate the polymer. The precipitate was collected and vacuum dried at 120 °C for 12 h to obtain the powdered solid polymer poly(siloxane-imide).
[0084] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran, add 20.46 mg (0.00015 mol) of ZnCl2, stir and react at 25 °C for 3 h, concentrate the reaction solution and pour it into a mold, evaporate the solvent and dry it under vacuum at 80 °C for 2 h to obtain a coordination crosslinked poly(siloxane-imide) thermoplastic elastomer. This material can be repeatedly dissolved and hot-pressed.
[0085] The elastomer material has the following characteristics: tensile strength of 39 MPa, elongation at break of 265%, and thermoplastic temperature of 124.7℃.
[0086] Comparative Example 1
[0087] A method for preparing a poly(siloxane-imide) thermoplastic elastomer includes the following steps:
[0088] (1) Under an argon atmosphere, 1332.72 mg (0.003 mol) of hexafluoroisopropyl phthalic anhydride (6FDA) was added to a three-necked flask equipped with a stirrer, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was complete, the reaction was stirred at 25 °C for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0089] (2) Under argon atmosphere and stirring conditions, 600.72 mg (0.003 mol) of 4,4'-diaminodiphenyl ether was added to the above poly(siloxane-amic acid) prepolymer solution in 5 portions (approximately 120 mg each time, with an interval of 10 min between each addition). After the addition was complete, the reaction was stirred at 25°C for 8 h to obtain a poly(siloxane-amic acid) solution. 235 μL (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185°C and stirred under argon atmosphere for 8 h. Finally, the polymer solution was added to a 1:1 mixture of anhydrous methanol and water to precipitate the polymer. The precipitate was collected and vacuum dried at 120°C for 12 h to obtain the powdered solid polymer poly(siloxane-imide).
[0090] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran, concentrate the reaction solution and pour it into a mold. After evaporating the solvent, vacuum dry at 80°C for 2 h to obtain an uncoordinated crosslinked poly(siloxane-imide) thermoplastic elastomer.
[0091] The elastomer material has the following characteristics: tensile strength of 23 MPa, elongation at break of 280%, and thermoplastic temperature of approximately 112.9℃.
[0092] The difference between this comparative example and Example 1 is that 3,5-diaminobenzoic acid was replaced with carboxyl-free phenylenediamine as a chain extender, and ionic coordination crosslinking was not introduced. Therefore, the strength and thermoplastic temperature of the resulting material were significantly reduced.
[0093] Comparative Example 2
[0094] A method for preparing a high-strength poly(siloxane-imide) thermosetting elastomer includes the following steps:
[0095] (1) Under an argon atmosphere, 1332.72 mg (0.003 mol) of hexafluoroisopropyl phthalic anhydride (6FDA) was added to a three-necked flask equipped with a stirrer, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was complete, the reaction was stirred at 25 °C for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0096] (2) Under argon atmosphere and stirring conditions, 600.72 mg (0.003 mol) of 4,4'-diaminodiphenyl ether was added to the above poly(siloxane-amic acid) prepolymer solution in 5 portions (about 120 mg each time, with an interval of 10 min between each addition). After the addition was completed, the reaction was stirred at 25 °C for 8 h to obtain a poly(siloxane-amic acid) solution. The poly(siloxane-amic acid) solution was precipitated in a large amount of water to obtain a large amount of white flocculent precipitate, which was then vacuum dried at 80 °C for 2 h to obtain the flocculent product.
[0097] (3) Dissolve the dried flocculent product in 15 ml of N-methylpyrrolidone and imide it according to the temperature program: 80℃ for 8 h, 120℃, 150℃, 200℃ and 250℃ for 1 h each to obtain a poly(siloxane-imide) thermosetting elastomer, which is basically completely insoluble and infusible.
[0098] The elastomer material has the following characteristics: the tensile strength is 32 MPa, the elongation at break is 123%, and because it is a thermosetting material, it has no thermoplastic temperature.
[0099] The difference between this comparative example and Example 1 is that 3,5-diaminobenzoic acid was replaced with carboxyl-free phenylenediamine as the chain extender, ionic coordination crosslinking was not introduced, and imidization was performed using a solid-state heating method. The material ultimately forms a covalently crosslinked network. Although there is no significant loss in tensile strength, elasticity is reduced, and thermoplasticity is lost.
[0100] Comparative Example 3
[0101] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps:
[0102] (1) Under an argon atmosphere, add 1332.72 mg (0.003 mol) of hexafluoroisopropyl phthalic anhydride (6FDA) to a three-necked flask equipped with a stirrer, add 18 ml of N-methylpyrrolidone and stir to dissolve. Under stirring, add 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw = 1030 g / mol) dissolved in 9 ml of tetrahydrofuran dropwise through a dropping funnel. Add the product dropwise to the above reaction solution. After the addition is complete, add 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid in three portions (approximately 150 mg each time, with a 10-minute interval between each addition) to the reaction system. After the addition is complete, stir the reaction at 25°C for 8 hours to obtain a poly(siloxane-amic acid) solution. Then, add 235 μL (0.002 mol) of isoquinoline to the reaction solution and heat the reaction to 185°C, stirring under argon atmosphere for 8 hours. Finally, add the polymer solution to a 1:1 mixture of anhydrous methanol and water to precipitate the product. Collect the precipitate and vacuum dry it at 120°C for 12 hours to obtain the powdered solid polymer poly(siloxane-imide).
[0103] (2) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran, add 20.46 mg (0.00015 mol) of ZnCl2, stir and react at 25 °C for 3 h, concentrate the reaction solution and pour it into a mold, evaporate the solvent and dry it under vacuum at 80 °C for 2 h to obtain a coordination crosslinked poly(siloxane-imide) thermoplastic elastomer. This material can be repeatedly dissolved and hot-pressed.
[0104] The elastomer material has the following characteristics: tensile strength of 18 MPa, elongation at break of 110%, and thermoplastic temperature of 116.8℃.
[0105] The difference between this comparative example and Example 1 is that prepolymerization and chain extension are basically carried out simultaneously. Since the formation of amic acid from acid anhydride and diamine is a reversible reaction, when prepolymerization and chain extension are carried out simultaneously, the polymer structure formed after reaching the reaction equilibrium of polyamic acid may deviate from the expected compound structure. Moreover, the polysiloxane with amino hydrocarbon end caps has relatively low polarity and is at a disadvantage in the competitive reaction, resulting in a significant reduction in the strength and thermoplastic temperature of the obtained material.
Claims
1. A high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer, characterized in that, The general structural formula is as follows: ; Formula (I) Where m, x, s, h, and n are all integers greater than or equal to 1; Ar1 and Ar2 are selected independently from or R1, R2, R3, and R4 are methyl groups; M is selected from Zn. 2+ ; The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer has a thermoplastic temperature of 120~155℃, a tensile strength ≥35MPa, and an elongation at break ≥150%. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer includes the following steps: (1) In a solvent, an aromatic dianhydride and an aminoalkyl-terminated polysiloxane are reacted to obtain a poly(siloxane-amic acid) prepolymer solution; the aromatic dianhydride is selected from hexafluoroisopropylphthalic anhydride or 4,4'-oxobisphthalic anhydride; the aminoalkyl-terminated polysiloxane is selected from bis(3-aminopropyl)-terminated polydimethylsiloxane; the weight-average molecular weight of the aminoalkyl-terminated polysiloxane is in the range of 500 or 1030 g / mol; (2) A carboxyl-substituted aromatic diamine is added to a poly(siloxane-amic acid) prepolymer solution and reacted to obtain a poly(siloxane-amic acid) solution; a catalyst is added and an imidization reaction is carried out, followed by precipitation and drying to obtain a solid polymer poly(siloxane-imide); the carboxyl-substituted aromatic diamine is selected from 3,5-diaminobenzoic acid; (3) The solid polymer poly(siloxane-imide) is dissolved in an organic solvent, a metal salt is added, and after reaction, the solvent is removed to obtain a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer; the metal salt is selected from zinc chloride; the molar ratio of the metal salt to the carboxyl-substituted aromatic diamine in step (2) is 1:7-20.
2. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that, In equation (I), 1 ≤ x ≤ 200, 1 ≤ s ≤ 20.
3. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that, Step (1) includes one or more of the following conditions: i. The solvent is a mixture of solvent A and solvent B, wherein the volume ratio of solvent A to solvent B is (1~5):(1~5); solvent A is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, methyl isobutyl ketone, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, dioxane, xylene or isopropanol; solvent B is selected from tetrahydrofuran, toluene, chloroform, dichloromethane, petroleum ether, n-hexane or ethyl acetate; ii. The total mass ratio of aromatic dianhydride and amino hydrocarbon-terminated polysiloxane to solvent is 50~200 g / L; iii. The molar ratio of aromatic dianhydride to amino hydrocarbon-terminated polysiloxane is (1-4):1; iv. The reaction temperature is 0~80℃, the reaction time is 1~24h, and the reaction is carried out under stirring conditions and inert gas protection. v. The preparation method of poly(siloxane-amic acid) prepolymer solution includes the following steps: dissolving aromatic dianhydride in solvent A, and adding dropwise a mixture of amino-terminated polysiloxane and solvent B under stirring conditions. After the addition is complete, the poly(siloxane-amic acid) prepolymer solution is obtained through reaction.
4. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 3, characterized in that, The reaction temperature is 20~30℃, the reaction time is 6~10h, and the inert gas is nitrogen or argon.
5. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that, Step (2) includes one or more of the following conditions: i. Aromatic diamines containing carboxyl groups are added to the reaction system in 2-3 portions, with an interval of 10-20 minutes between each addition; ii. The molar ratio of the carboxyl-substituted aromatic diamine to the aromatic dianhydride in step (1) is 1-1.1:1; iii. The reaction temperature is 0~80℃, the reaction time is 1~24h, and the reaction is carried out under stirring conditions and inert gas protection. iv. The catalyst is selected from organic amines, organophosphorus compounds, pyridines, benzopyridines, amidines, or organic guanidines; v. The molar ratio of the catalyst to the carboxyl-substituted aromatic diamine is 1:(1~2). vi. The imidization reaction temperature is 60~200℃, the imidization reaction time is 1~24h, and the imidization reaction is carried out under stirring conditions and inert gas protection. vii. Precipitation is carried out using a mixed solution of anhydrous methanol and water, wherein the volume ratio of anhydrous methanol to water is 1:
1.
6. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that, Includes one or more of the following conditions: i. The reaction temperature is 20~30℃, the reaction time is 6~10h, and the inert gas is nitrogen or argon; ii. The catalyst is selected from one or more of triethylamine, hexamethylenetetramine, pyridine, or isoquinoline; iii. The imidization reaction temperature is 170~190℃, the imidization reaction time is 6~10h, and the inert gas is nitrogen or argon.
7. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that, Step (3) includes one or more of the following conditions: i. The organic solvent is selected from one or more of tetrahydrofuran, ethyl acetate, isopropanol, toluene, chloroform, dichloromethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dioxane, or xylene; ii. The molar ratio of the carboxyl-substituted aromatic diamine in step (2) to the volume ratio of the organic solvent in step (3) is 0.1-1 mol / L; iii. The reaction temperature is 20~50℃, the reaction time is 1~3h, and the reaction is carried out under stirring conditions.
Citation Information
Patent Citations
Organosilicon polyimide-polyurea basic polymer, elastomer prepared therefrom, preparation and use thereof
CN101469063A
Organic silicon modified polyimide resin composition and application thereof
CN109517172A
Preparation method of high-temperature-resistant polyimide modified PDMS (polydimethylsiloxane) silicone resin
CN109679495A
Multifunctional polysiloxane thermoplastic elastomer as well as preparation method and application thereof
CN111154107A
Polymer, composition comprising same, and polysiloxane-polyimide material
CN114685790A
